3D photography is as accurate as digital planimetry tracing in determining burn wound area. Issue 1 (February 2015) - Stockton, K.A.; McMillan, C.M.; Storey, K.J.; David, M.C.; Kimble, R.M.
Abstract Background In the paediatric population careful attention needs to be made concerning techniques utilised for wound assessment to minimise discomfort and stress to the child. Aim To investigate whether 3D photography is a valid measure of burn wound area in children compared to the current clinical gold standard method of digital planimetry using Visitrak™. Method Twenty-five children presenting to the Stuart Pegg Paediatric Burn Centre for burn dressing change following acute burn injury were included in the study. Burn wound area measurement was undertaken using both digital planimetry (Visitrak™ system) and 3D camera analysis. Inter-rater reliability of the 3D camera software was determined by three investigators independently assessing the burn wound area. Results A comparison of wound area was assessed using intraclass correlation co-efficients (ICC) which demonstrated excellent agreement 0.994 (CI 0.986, 0.997). Inter-rater reliability measured using ICC 0.989 (95% CI 0.979, 0.995) demonstrated excellent inter-rater reliability. Time taken to map the wound was significantly quicker using the camera at bedside compared to Visitrak™ 14.68 (7.00) s versus 36.84 (23.51) s (p < 0.001). In contrast, analysing wound area was significantly quicker using the Visitrak™ tablet compared to Dermapix® software for the 3D Images 31.36 (19.67) s versus 179.48 (56.86) s (p < 0.001). Conclusion This study demonstrates that images taken with the 3D LifeViz™ camera and assessed with Dermapix® software is a reliable method for wound area assessment in the acute paediatric burn setting.